Access to Healthcare in Remittance-Receiving Household: A Qualitative Study of Health Seeking Behaviour among the Esan People of South-South Nigeria - Alenkhe, Augustine Odianonsen (NIU Journal of Social Sciences, 2025)
Remittances represent a vital livelihood strategy and informal social protection mechanism that alleviates financial barriers to healthcare access in developing contexts. Despite the improved healthcare utilization associated with remittance inflows, persistent structural weaknesses within Nigeria’s healthcare system continue to influence patterns of access and use. This study examines the influence of remittances on access to and utilization of healthcare services among remittance-receiving households in southern Nigeria, with specific focus on Esan communities in Edo State. Adopting an expository research design, the study employed a qualitative approach to generate in-depth understanding of household health-seeking behaviour. Data were collected through in-depth interviews with 32 household heads selected from two local government areas in the Edo Central Senatorial District using a multi-stage sampling technique. The data were analyzed using content analysis. Findings reveal that remittances significantly enhance the utilization of modern healthcare services by reducing financial constraints and enabling timely access to professional medical care. However, healthcare utilization is also shaped by interacting factors such as income stability, social status, cultural beliefs, geographic proximity to health facilities, availability of skilled health personnel, and emergency health needs. The study concludes that while remittances improve healthcare access, they function as complementary mechanisms within a health system characterized by enduring structural inequalities. Keywords: Healthcare services, Health seeking behaviour, Household head, Remittances,